Optimization of carboxymethyl cellulose-gum Arab-based hydrogel beads for anticancer drugs delivery - Ghawanmeh, Abdullah A.; Tan, Ling Ling; Ali, Gomaa A.M.; Assiri, Mohammed Ali; Chong, Kwok Feng (Elsevier B.V., 2024)
Response surface methodology was successfully utilized to optimize the amounts of carboxymethyl cellulose (CMC) and gum Arab (GA) to fabricate hydrogel beads for the delivery of anticancer drugs. Drug encapsulation efficiency process (%DEE) and cumulative release (%R8h) of hydrogel beads were investigated with different amounts of CMC and GA with Fe (III) cross-linker. The numerical validation resulted in an optimized nanocomposite of CMC (99.61 mg) and GA (77.84 mg) with a DEE of 55.70 ± 2.15 % and R8h of 44.78 ± 0.27 %. The characterization approaches indicated the successful formation of this nanocomposite. The swelling behavior of the beads was triggered by pH change, and the drug release profile showed prolonged sustainable release that followed the Higuchi model with a non-Fickian mechanism. This nanocomposite could be a promising nanocarrier for drug loading and its controlled delivery.